2018
DOI: 10.1007/s13201-018-0812-9
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of depth-averaged velocity in an open channel flow

Abstract: This paper presents a new methodology to predict the depth-averaged velocity along the lateral direction in an open channel flow. The novelty of this work is to determine the point velocity and estimate the discharge capacity by knowing the geometrical parameters at a section of an open channel flow. Experimental investigations have been undertaken in trapezoidal and rectangular channels to observe the variation of local velocities along both the vertical and transverse directions at testing sections. For diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Before analyzing the ADV data, possible spectral analysis has been done. The measured data were despiked by an algorithm based on the acceleration thresholding strategy (Goring and Nikora 2002;Khuntia et al 2018b), which was fit for recognizing and substituting spikes in two stages. The threshold values (=1-1.5) for despiking were determined by trial and error basis, for which the velocity power spectra gave an acceptable fit to the Kolmogorov -5/3 scaling-law in the inertial subrange.…”
Section: Resultsmentioning
confidence: 99%
“…Before analyzing the ADV data, possible spectral analysis has been done. The measured data were despiked by an algorithm based on the acceleration thresholding strategy (Goring and Nikora 2002;Khuntia et al 2018b), which was fit for recognizing and substituting spikes in two stages. The threshold values (=1-1.5) for despiking were determined by trial and error basis, for which the velocity power spectra gave an acceptable fit to the Kolmogorov -5/3 scaling-law in the inertial subrange.…”
Section: Resultsmentioning
confidence: 99%
“…The test section is 10 m from upstream, where flow stabilizes and uniform flow is observed. A tailgate is installed downstream to achieve uniform flow conditions (Khuntia et al 2018(Khuntia et al , 2019.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the model was more suitable for the prediction of bend flow velocity of 60 o [ 2 ]. Khuntia et al [ 3 ] proposed to use multivariate regression to analyze and predict the river velocity and found that the machine learning algorithm performed better than the traditional Shiono and Knight methods [ 3 ]. Based on particle tracking velocimetry, Eltner et al [ 4 ] collected and estimated River images.…”
Section: Related Workmentioning
confidence: 99%